Iron-based nanocatalyst for the acceptorless dehydrogenation reactions - Jaiswal, Garima; Landge, Vinod G.; Jagadeesan, Dinesh; Balaraman, Ekambaram (Nature Communications, 2017)
Development of sustainable catalytic systems for fundamentally important synthetic transformations and energy storage applications is an intellectually stimulating challenge. Catalytic dehydrogenation of feedstock chemicals, such as alcohols and amines to value-added products with the concomitant generation of dihydrogen is of much interest in the context of hydrogen economy and is an effective alternative to the classical oxidation reactions. Despite a number of homogeneous catalysts being identified for the acceptorless dehydrogenation, the use of high price and limited availability of precious metals and poor recovery of the catalyst have spurred interest in catalysis with more earth-abundant alternatives, especially iron. However, no report has described a reusable iron-based heterogeneous catalyst for oxidant-free and acceptorless dehydrogenation reactions. Here we replace expensive noble metal catalysts with an inexpensive, benign, and sustainable nanoscale iron catalyst for the efficient acceptorless dehydrogenation of N-heterocycles and alcohols with liberation of hydrogen gas.

Iron-carbon nanohybrid particles as environmentally benign electrode for supercapacitor - Ratha, Satyajit; Vernekar, Dnyanesh; Sivaneri, Kavin; Jagadeesan, Dinesh; Rout, Chandra Sekhar (Journal of Solid State Electrochemistry, 2017)
In this work, we report the synthesis and electrode applications of iron-carbon nanohybrid particles prepared by carbonization of a nanocomposite of FeOOH nanoneedles and melamine-formaldehyde resin. The chemical composition and microstructure of the material have been characterized using ICP-AES, FT-IR, XRD, FESEM, TEM and XPS. The supercapacitor properties of the MF-Fe-C are studied in detail. A thorough comparison of the supercapacitor performances of MF-Fe-C and bare MF-C has been carried out through detailed electrochemical characterisations employing both two and three-electrode techniques. The nanohybrid showed an enhanced energy density of 127.75 WhKg⁻¹, specific capacitance of ∼408 F g⁻¹ at 1 mVs⁻¹ scan rate, and excellent cyclic stability even after 1000 charge-discharge cycles, making it an intriguing material for high energy density supercapacitor devices.